Systematic treatment of Sago effluent using sequencing batch reactor (SBR) - Jazliana, Binti Johan. (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study was conducted to compare the effectiveness of Sequencing Batch Reactor (SBR) to treat filtered sago effluent using single and double inoculums of the microorganism (Bak Wira MP300). The aeration was supplied and set on timer with time on/time off at 15 min onll5 min off. Aeration pump was turned off on day 4 and day 8 to undergo sedimentation process in order to form the sludge. Sampling was performed everyday for 8 days. Sago effluent typically contains high organic solids (35%), low pH (3.9-4.5) with some starch and glucose. Initial observation showed that single inoculum enhances higher Chemical Oxygen Demand (COD) removal which is about 74.61 % after 7 days and produced 54.57% of Total Suspended Solids (TSS) on day 0 after inoculation. Double inoculation showed that the higher COD removal is about 51.52% after 7 days and produced 40.97% ofTSS after 1 day.